2010
DOI: 10.1111/j.1460-9568.2010.07260.x
|View full text |Cite
|
Sign up to set email alerts
|

The neurobiology of amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis is a degenerative disease affecting the motor neurons. In spite of our growing insights into its biology, it remains a lethal condition. The identification of the cause of several of the familial forms of ALS allowed generation of models to study this disease both in vitro and in vivo. Here, we summarize what is known about the pathogenic mechanisms of ALS induced by hereditary mutations, and attempt to identify the relevance of these findings for understanding the pathogenic mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 286 publications
2
58
0
1
Order By: Relevance
“…Consistent with this idea, it has been shown that mutations in transport-related genes can result in neurodegenerative phenotypes in mice and humans (3,4). Because transport deficits have been reported in many neurodegenerative diseases, including Alzheimer's disease, Huntington's disease, and amyotrophic lateral sclerosis (ALS) (5)(6)(7)(8), it is commonly assumed that disturbances in axonal transport are key pathological events that contribute to neurodegeneration (9)(10)(11). However, the causal relationship of axonal transport disturbances to degeneration remains unclear.…”
mentioning
confidence: 71%
“…Consistent with this idea, it has been shown that mutations in transport-related genes can result in neurodegenerative phenotypes in mice and humans (3,4). Because transport deficits have been reported in many neurodegenerative diseases, including Alzheimer's disease, Huntington's disease, and amyotrophic lateral sclerosis (ALS) (5)(6)(7)(8), it is commonly assumed that disturbances in axonal transport are key pathological events that contribute to neurodegeneration (9)(10)(11). However, the causal relationship of axonal transport disturbances to degeneration remains unclear.…”
mentioning
confidence: 71%
“…4 Numerous hypotheses for the pathogenesis of ALS have been proposed, which include glutamate toxicity, oxidative stress, mitochondrial dysfunction, autoimmune mechanisms, protein aggregation, and glial involvement. 5,6 Recently, it was postulated that ALS is a neurovascular disease and that the impairment of the bloodspinal cord barrier is one of the first pathologic events. 7 The blood-spinal cord barrier separates the circulating blood from the spinal cord parenchyma and comprises endothelial cells, astrocytes, and pericytes.…”
Section: Introductionmentioning
confidence: 99%
“…This disease is characterized by the selective death of motor neurons in the brain (upper motor neurons) and spinal cord (lower motor neurons), resulting in the paralysis of voluntary muscles (2)(3)(4)(5)(6)(7)(8)(9). Gene defects are detected in ~5-10% of ALS patients (familial ALS).…”
Section: Introductionmentioning
confidence: 99%